Increased prevalence of urticarial diseases and antihistamine/corticosteroid consumption in patients with attention-deficit/hyperactivity disorder - Ariel Israel; Shai Ashkenazi; Eugene Merzon; Ilan Green; Avivit Golan-Cohen; Eli Magen; Shlomo Vinker; Akim Geishin; Iris Manor; Abraham Weizman (BMJ Mental Health)
Objectives This nationwide cohort study investigated the association between attention-deficit/hyperactivity disorder (ADHD) and various types of urticarial diseases.Methods We conducted a population-based cohort study using data from Leumit Health Services (LHS), a health maintenance organisation in Israel. The study population consisted of all members of LHS between 1 January 2002 and 30 November 2022 aged 5–18 years. Diagnoses of ADHD and urticarial diseases were based on International Classification of Diseases, 9th Edition codes. The study group consisted of subjects with ADHD, while matched controls were randomly selected non-ADHD subjects (2:1 ratio).Findings Demographic characteristics of ADHD (n=18 558) and control (n=37 116) groups were well-matched, with no significant socio-demographic differences. A significantly higher prevalence of various subtypes of urticarial diseases was found in the ADHD group compared with the control group. Specifically, urticaria (5.00% vs 4.22%, OR (95% CI) 1.19 (1.10 to 1.30), p<0.001), allergic urticaria (3.26% vs 2.73%, OR (95% CI) 1.20 (1.08 to 1.33), p<0.001). Inducible forms of urticaria did not show significant differences between the groups. The ADHD group had a higher use of systemic and topical antihistamines and systemic corticosteroids.Conclusions Various urticarial diseases are more prevalent in individuals with ADHD, possibly due to shared genetic factors, immune system dysfunction, or environmental triggers.Clinical implications This study suggests an association between ADHD and some urticaria subtypes. Physicians should be aware of this association and its public health implications.